From the one to the multiple: Alternatives to say and think the world today - Zuluaga Mesa, David Esteban (2025)
The article reflects on the role of philosophy and the philosopher in today's world. It relates the change of method of the philosophy of the second Wittgenstein with hypertext as a possibility to build multiple meanings in a dynamic and complex world.